2023
DOI: 10.1039/d2cs00647b
|View full text |Cite
|
Sign up to set email alerts
|

Materials engineering strategies for cancer vaccine adjuvant development

Abstract: In this Review, we have summarized advances in the development of cancer vaccine adjuvants, including chemically engineered molecular agonists, versatile self-adjuvanting materials, and genetically engineered bio-derived materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 121 publications
0
17
0
Order By: Relevance
“…Subsequently, Alexander Glenny first reported that diphtheria toxoid prepared by aluminum salt precipitation process can induce and produce stronger immune efficacy, and they experimentally demonstrated the auxiliary role of aluminum salts in immunotherapy. 55 In humans, adjuvants are completely foreign, have minimal toxicity and have long-lasting immune effects of their own; for more than 80 years, only aluminum salts have been used as adjuvants in vaccines to induce humoral responses due to (i) increased biological or immune half-life of vaccine antigens (storage effect); (ii) improved delivery of antigens to APCs for antigen processing and further presentation; and (iii) induction of the production of immunoregulatory factors. 56 However, aluminum salts as adjuvants have little effect on Th1 type reactions, which help resist many pathogens and can be used to enhance Th2 driven antibody reactions; therefore, over a period of 20 years, vaccines have introduced many new adjuvants, such as AS01, AS03, AS04, CpG oligonucleotides (ODN), and MF59, with Montanide ISA-51 and granulocyte macrophage colony stimulating factor (GM-CSF) being the most widely used in cancer vaccines.…”
Section: Definition Composition and Classification Of Cancer Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, Alexander Glenny first reported that diphtheria toxoid prepared by aluminum salt precipitation process can induce and produce stronger immune efficacy, and they experimentally demonstrated the auxiliary role of aluminum salts in immunotherapy. 55 In humans, adjuvants are completely foreign, have minimal toxicity and have long-lasting immune effects of their own; for more than 80 years, only aluminum salts have been used as adjuvants in vaccines to induce humoral responses due to (i) increased biological or immune half-life of vaccine antigens (storage effect); (ii) improved delivery of antigens to APCs for antigen processing and further presentation; and (iii) induction of the production of immunoregulatory factors. 56 However, aluminum salts as adjuvants have little effect on Th1 type reactions, which help resist many pathogens and can be used to enhance Th2 driven antibody reactions; therefore, over a period of 20 years, vaccines have introduced many new adjuvants, such as AS01, AS03, AS04, CpG oligonucleotides (ODN), and MF59, with Montanide ISA-51 and granulocyte macrophage colony stimulating factor (GM-CSF) being the most widely used in cancer vaccines.…”
Section: Definition Composition and Classification Of Cancer Vaccinesmentioning
confidence: 99%
“…The concept of adjuvants was proposed by Gaston Ramon in 1925 when he discovered that sterile additives could increase the production of antibodies in animals. Subsequently, Alexander Glenny first reported that diphtheria toxoid prepared by aluminum salt precipitation process can induce and produce stronger immune efficacy, and they experimentally demonstrated the auxiliary role of aluminum salts in immunotherapy . In humans, adjuvants are completely foreign, have minimal toxicity and have long-lasting immune effects of their own; for more than 80 years, only aluminum salts have been used as adjuvants in vaccines to induce humoral responses due to (i) increased biological or immune half-life of vaccine antigens (storage effect); (ii) improved delivery of antigens to APCs for antigen processing and further presentation; and (iii) induction of the production of immunoregulatory factors .…”
Section: Definition Composition and Classification Of Cancer Vaccinesmentioning
confidence: 99%
“…In addition to introducing additional adjuvants, some delivery vectors have self-adjuvant properties and can serve as both vaccine carrier and adjuvant simultaneously, such as lipid-like materials C161, DOTAP/DP7-C59, and LNPs. Some of them can be used as adjuvants, similar to PAMP. , Immunostimulants (such as PRRs) can be used with delivery systems because they recognize molecules that are often present in pathogens and help generate a robust immune response. Some recent studies of LNPs/mRNA vaccines appear to show the advantages of carriers with self-adjuvant properties .…”
Section: Construction Of Mrna Cancer Vaccinementioning
confidence: 99%
“…Some of them can be used as adjuvants, similar to PAMP. 75,76 Immunostimulants (such as PRRs) can be used with delivery systems because they recognize molecules that are often present in pathogens and help generate a robust immune response. Some recent studies of LNPs/mRNA vaccines appear to show the advantages of carriers with self-adjuvant properties.…”
Section: ′ Cap and Poly(a)mentioning
confidence: 99%
“…Cancer vaccine represents a promising strategy that has emerged in recent years. , After a single or several subcutaneous injections, a cancer vaccine could elicit efficient tumor antigen-specific immune responses systematically and establish immune memory effects, thus clearing metastatic tumor cells and preventing tumor relapse, which provides a promising alternative solution to breast cancer postoperation management. However, the current immune responses to therapeutic cancer vaccines remain low. One of the most important reasons is the lack of proper carriers or adjuvants that can effectively deliver and stimulate the cellular immune responses that anticancer therapy needs. , To achieve this goal, precise control of both the spatial and temporal aspects of the vaccine kinetics is necessary. , In terms of spatial control, the antigens must be delivered to the paracortical regions of the lymph nodes to facilitate antigen presentation from dendritic cells (DCs) to T cells. In terms of temporal control, sustained antigen stimulation is viewed to be more effective for vaccine efficacy. ,, Unfortunately, a vaccine adjuvant that fulfills the above requirements is still lacking.…”
mentioning
confidence: 99%